Derivatives: the forward - Mavila Hinojoza, Daniel (2001)
In the present article is exposed the importance and the mechanisms for the access to the markets of derived products, where contracts are negociated to future types of interest, foreign currencies and market indexes; options on foreign currencies, types of interest, market indexes and stocks, as well as financial exchanges.